Application of multiple strategies to efficiently break seed dormancy of permanently odd pentaploid rose hip (Rosa canina l.) under in vitro conditions - Hajyzadeh, Mortaza (My University, 2022)
Rosehip (Rosa canina L.) is an important medicinal, and ornamental plant species with high commercial value. Its sugars, phenolics, organic acids, water-soluble vitamins, and mineral contents composition varies depending on environmental conditions and genetics. The plant is also used as a perfect rootstock for many rose cultivars. Seed proliferation is extremely difficult because of multiple endogenous and exogenous dormancy factors. There is a need to breed standard rosehip cultivars rootstock developments with desired characteristics and outperforming yields in fields. The study aimed to break the seed dormancy of rosehip under in vitro conditions by application of multiple strategies in an efficient manner. The seeds were treated with different doses of GA?, scarified mechanically, stratified on agar solidified MS medium containing GA? singly or in combinations of the two each or three treatments, and subjecting them to the regulated physiological treatment of alternating warm/chilling and cold/dark treatments in parallel for 21 d ensued by 18 d warm/light treatments. It was noted that the rosehip seeds could be germinated variably if the scarified seeds were stratified on agar solidified MS medium with or without GA3. Optimum seed germination (80.00- 85.00%) was noted when the three treatments were combined and the seeds were subjected to regulated and alternating warm and chilling treatments for 21 d leaving them for 18 d in warm/light. These results are very important and could be utilized in breeding and multiplication programs to develop new rosehip fruit and rootstock cultivars.
Keywords: Breeding; Germination; Stratification; Diversity; Scarification